The Effect of Communication and Policy-Making to Teacher’s Performance on Strategic Madrasah Leadership during Pandemic Covid-19 - Ahmadi Ahmadi; Ahmad Romadlon (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractCommunication and policy making can either increase or decrease performances. This study aims to measure whether communication and policy making have impacts on teachers’ performance. This research is a quantitative study using proportional random sampling technique. The research data were obtained through a questionnaire and were then analyzed by the t-test and multiple linear regression analysis. The research results showed that both communication and policy-making styles had a significant impact on teachers’ performance, and simultaneously the communication style and policy-making style had an impact on teacher performance by 71.1%. Thus, the strategic leadership of madrasa principals at the Islamic Elementary School level should be taken into account to formulate differentiation and diversification strategies of communication policies, especially during the Covid-19 pandemic.Keywords: assessment, communication skills, elementary school students. AbstrakKomunikasi dan pengambilan kebijakan dapat meningkatkan kinerja atau sebaliknya. Penelitian ini bertujuan untuk mengukur apakah hal tersebut berdampak terhadap kinerja guru. Penelitian ini merupakan penelitian kuantitatif dengan teknik pengambilan sampel menggunakan proportional random sampling. Data hasil penelitian diperoleh melalui kuesioner dan dianalisis dengan rumus uji t-tests dan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa gaya komunikasi secara signifikan berdampak terhadap kinerja guru, gaya pengambilan kebijakan secara signifikan berdampak terhadap kinerja guru, dan secara simultan gaya komunikasi dan gaya pengambilan kebijakan berdampak terhadap kinerja guru sebesar 71.1%. Sehingga, kepemimpinan kepala madrasah yang strategik di tingkat pendidikan dasar Islam seharusnya dipandang untuk memformulasikan strategi diferensiasi dan diversifikasi pada kebijakan komunikasi lebih lanjut, apalagi pada masa pandemi Covid-19.Kata kunci: penilaian, kemampuan komunikasi, siswa sekolah dasar.